KAJIAN SEMIOTIKA PADA DESAIN KEMASAN PRODUK PERAWATAN KULIT WANITA - Talitha Alysia Onggo; Devanny Gumulya (Universitas Bunda Mulia, 2016)
Study about packaging design within the context of packaging design communication is an interesting area to be researched; because there are designers’ intended impressions and users’ realized impressions of products. The paper tries to relate and evaluate the customer perceptions and design element used by designer to construct meaning by using semiotic theory. Local skin care packaging is taken as study case, because skin care product is a fast growing industry in Indonesia, proven there are numerous local brands offered in supermarket and often they changing their packaging. Therefore a study is needed for evaluating consumer perception on Indonesian skin care packaging, whether existing packaging already convey the product benefits effectively. A combination of literature study and quantitative data from semi structured questionnaires will collect experiential data accessing participant engagement in perceiving a range of packaging samples from selected Indonesian skin care brand: Martha Tilaar, Sariayu, Viva, and Citra. The study tries to provide design recommendation for future packaging design.Keywords : Visual element, packaging design, semiotics